Proving the identity of a complementing gene in Aspergillus nidulans by tandem integration and loop-out repair - S GW Kaminskyj (Fungal Genetics Reports, 2000)
This reports a convenient way for tagging a complementing sequence (gene or gene fragment) for use in tandem integration/loopout repair. It was used to verify cloning of the hypA locus. The backbone of a hypA1-complementing plasmid was tagged with pLH1, a Tn5 transposon having a diagnostic BamH1 fragment containing argB+. This was transformed into a hypA1, argB2 strain of A. nidulans. Transformants with an integrated copy of the tagged plasmid were allowed to self-mate. Given integration at hypA, and that the plasmid sequence was from the hypA locus, this led to loopout repair of the hypA1 defect with concomitant loss of argB+.